2002
DOI: 10.1038/sj.mp.4001092
|View full text |Cite
|
Sign up to set email alerts
|

Synaptosomal-associated protein 25 (SNAP-25) and attention deficit hyperactivity disorder (ADHD): evidence of linkage and association in the Irish population

Abstract: Attention deficit hyperactivity disorder (ADHD) is a neuropsychiatric condition characterized by hyperactive-impulsive behaviour and persistent inattention. Individuals with this condition experience social and academic dysfunction. Although the aetiology of ADHD is not known, it is postulated that a developmental failure in the brain mechanism that underlies self-control and inhibition is involved.2 ADHD affects approximately 3-6% of children and adolescents from different geographical regions worldwide.3 Boy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
107
0
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(111 citation statements)
references
References 27 publications
3
107
0
1
Order By: Relevance
“…40 Emerging evidence from currently published association/linkage studies has further implicated SNAP25 in ADHD. 2 This work replicated previous reports of associations for the regions of 3 0 -untranslated region (UTR), introns 1 and 7, [41][42][43][44][45] although a different set of variants were included. There is, however, a lack of overlap with the associated SNPs identified in the IMAGE sample.…”
Section: Discussionsupporting
confidence: 82%
“…40 Emerging evidence from currently published association/linkage studies has further implicated SNAP25 in ADHD. 2 This work replicated previous reports of associations for the regions of 3 0 -untranslated region (UTR), introns 1 and 7, [41][42][43][44][45] although a different set of variants were included. There is, however, a lack of overlap with the associated SNPs identified in the IMAGE sample.…”
Section: Discussionsupporting
confidence: 82%
“…This deletion causes a 50% reduction in the expression of SNAP-25, a presynaptic protein involved in calcium-triggered neurotransmitter release (Hess et al, 1992). Identification of the Snap25 gene defect in these mice provided a candidate gene for studies in humans that revealed an association between SNAP25 and ADHD (Barr et al, 2000, Brophy et al, 2002, Mill et al, 2002, Kustanovich et al, 2003. Although such studies show associations and not direct causal relationships between a genetic locus and a disorder, the association between SNAP25 and ADHD suggests that coloboma mice have etiological validity.…”
Section: Introductionmentioning
confidence: 99%
“…45,48,49 Because of the observed increased hyperactivity of hemizygous Coloboma mice, the role of SNAP-25 in attention deficit hyperactivity disorder (ADHD) has been tested in several studies. [50][51][52][53][54] All, except one (Xu et al 54 ), report a significant association of SNAP-25 with ADHD in humans. The exact role of SNAP-25 in ADHD, however, remains unknown.…”
mentioning
confidence: 99%